FROZEN SHOULDER PADA PASIEN LONG COVID: TINJAUAN KASUS DENGAN PENDEKATAN TERAPI BODY SPACE MEDICINE DI MONG KOK, KOWLOON, HONGKONG - Sugiarti Sugiarti; Hilman Rama Pratama; Ita Susanti (Journal of Innovation Research and Knowledge, 2026)
Sugiarti / 20220302700234 / 2026 / Frozen Shoulder in a Long COVID Patient: A Case Review Using the Body Space Medicine Therapeutic Approach in Mong Kok, Kowloon, Hong Kong / Ir. Hilman Rama Pratama, S.Ud., S.Tr.Kes., M.Pd. Frozen shoulder or adhesive capsulitis is a condition characterized by pain and limited range of motion in the shoulder joint, which may be triggered by various factors, including post-COVID-19 conditions. Persistent inflammation and reduced physical activity during the recovery phase can lead to joint stiffness and functional impairment. Body Space Medicine (BSM) is a therapeutic approach based on the concept of body space and energy circulation (Gong Zhuan), aiming to reduce energy stagnation and restore overall body function. This study aimed to determine the effectiveness of BSM therapy in reducing pain and improving range of motion in patients with post-COVID-19 frozen shoulder. The method used was a case study involving three patients who underwent four therapy sessions over two weeks, combined with self-therapy through Dong Yi Gong exercises. Evaluation parameters included the Numeric Rating Scale (NRS), Range of Motion (ROM), vital signs, and tongue examination before and after therapy. The results showed a significant reduction in pain intensity from moderate–severe to mild or minimal levels, along with improvements in shoulder range of motion approaching normal. Tongue examination also indicated improvements in internal body condition, reflected by a healthier color, thinner coating, and smoother median line. Additionally, patients reported better sleep quality, increased vitality, and improved daily functional activities.